PERKEMBANGAN OTAK DAN PERAN NUTRISI DALAM MENDUKUNG PRESTASI BELAJAR SISWA SEKOLAH DASAR - Ismasnawat; Rosniati Hakim; Dasrizal D; Ahmad Lahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the relationship between brain development and the role of nutrition in supporting primary school students' learning achievement. The issue raised is how brain development factors, which are influenced by nutritional intake, can affect children's cognitive abilities and spirituality. The methodology used in this research is a qualitative approach with literature analysis that links concepts in the Qur'an with recent neuroscience findings. Data was collected from various sources, including previous research and relevant Qur'anic commentaries. The results showed that the development of the human brain has a unique position and functions as the center of thinking activity which is greatly influenced by the nutrients received. This study concludes that meeting the needs of proper nutrition is essential to optimize brain development and improve learning achievement of primary school students, and emphasizes the need for more attention to children's diet in the context of education.